2017
DOI: 10.1002/jum.14462
|View full text |Cite
|
Sign up to set email alerts
|

Non‐Immune Hydrops Fetalis: Do Placentomegaly and Polyhydramnios Matter?

Abstract: Compared to NIHF alone, pregnancies with NIHF and P/PM had a lower risk of IUFD and were at increased risk of PTB (<37 and <34 weeks) and spontaneous PTB. This information may help providers in counseling patients with NIHF and supports the need for close antenatal surveillance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 22 publications
1
12
0
5
Order By: Relevance
“…In our study, a considerable proportion of fetuses with pleural effusion had polyhydramnios, and therefore, it could be argued that they have a higher risk of preterm delivery and neonatal death. This has been previously reported by Berger et al [14] who showed a higher prevalence of preterm delivery <34 weeks of gestation among hydropic fetuses with polyhydramnios (60% 60/100) as compared to hydropic fetuses without polyhydramnios (28.6% 6/21, p = 0.01). Whether polyhydramnios is associated with a short cervix has been studied by several authors with controversial results.…”
Section: Discussionsupporting
confidence: 86%
“…In our study, a considerable proportion of fetuses with pleural effusion had polyhydramnios, and therefore, it could be argued that they have a higher risk of preterm delivery and neonatal death. This has been previously reported by Berger et al [14] who showed a higher prevalence of preterm delivery <34 weeks of gestation among hydropic fetuses with polyhydramnios (60% 60/100) as compared to hydropic fetuses without polyhydramnios (28.6% 6/21, p = 0.01). Whether polyhydramnios is associated with a short cervix has been studied by several authors with controversial results.…”
Section: Discussionsupporting
confidence: 86%
“…The overall risk of PTB in our study (86%) was higher than previously reported (66-76%). 4,5,13,14 Because many of the previously published studies on outcomes of hydropic pregnancies included smaller cohorts of patients who delivered many years ago, it is possible that changing protocols for antenatal management with serial ultrasounds and nonstress testing are partially responsible for an increase in PTB, particularly given our finding that most PTBs were iatrogenic for fetal indications. Advances in neonatal care and an increasing expertise in the care of premature newborns may also have contributed to the greater frequency of PTB in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…One factor underlying spontaneous PTB may be polyhydramnios, which is known to complicate NIHF pregnancies and may predispose to PTB. 4,7,8 Preeclampsia is also associated with NIHF pregnancies and its development often necessitates medically indicated delivery. 9 Additional risk factors for PTB may include underlying fetal genetic disorders, fetal distress, and earlier diagnosis of fetal fluid collections.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, NIHF presents a poor prognosis that varies from preterm birth to intrauterine fetal demise (IUFD), stillbirth, neonatal morbidity, and mortality [1,[9][10][11]. The prognosis of NIHF depends on the etiology and gestational age at the time of diagnosis and delivery [12].…”
Section: Introductionmentioning
confidence: 99%